Comparative Analysis of Employment Trends in the Labor Market of Saudi Arabia: A Case Study, 2017 to 2022 - Aljohani, Mohammed (Eximia, 2023)
This study analyzes employment trends in the Saudi Arabia labor market from 2017 to 2022, with a special focus on Saudi, non-Saudi workers and gender proportion. The study uses data collected from the Saudi Arabian General Statistics Authority, presenting it in the form of tables and graphs. Regression analysis reveals that despite fluctuations, a steady increase is evident in the number of workers in the labor market over the years depicted, with a significant rise after the COVID pandemic. A majority of workers are non-Saudi with a slight increase in the number of Saudi workers each year, indicating high demand for foreign labor. This is typical in the context of many industries in the Saudi Kingdom. Additionally, the number of male workers is higher than the number of female workers, also not an unusual statistic. Yet, both of these features have been poised to change, as the Saudi government has sought to provide more jobs for Saudi nationals and recruit many more female workers, including professionals, into the labor force (Vision 2030, Saudi Arabian Government, 2015). The study concludes that the labor market in Saudi Arabia is growing and that there is a need to promote Saudization in the workplace and bolster opportunities for women to participate.